Passages de frontières. Le voyage de la jeune mariée dans la haute noblesse des temps modernes (XVe-XVIIIe siècle) - Christiane Coester (Genre & Histoire)
While French historians have tended to focus on the nuptial trips of the Spanish infantes to the Kingdom of France as well as that of Marie-Antoinette in 1770, such trips to the residence of the future spouse were common in Europe from the 15th to the 18th century. Only one normative text describing such trips exists (that of Diomeda Carafa, De institutione vivendi, 1476), but numerous other sources shed light on these one-way trips (correspondences, travel memoirs, newspapers, brochures, princely account books). Following a presentation of the variety of such trips, this article focuses on the classic example of the young women who leaves her parental home for that of her future spouse, following a series of codified steps. One of the most significant moments in this trip is the moment when she crosses the border and is confronted by the range of cultural differences (imagined or otherwise), while at the same time changing her status from that of young girl to wife. Once arrived in her spouse’s court, the fiancée had to adopt the reigning dress codes and hairstyles, not only to show her desire for integration but also her desire to please her husband. The analysis of these nuptial trips throughout Europe shows a number of commonalities. The process of individual transformation is part of a broader movement of exchange between the courts. The move involved more than spatial displacement but also a change in cultural references (language, fashion, food, etc.) which was often painful for the young women, even if a number of women, such as Anna d’Este and Anne of Austria, successfully integrated into their new courts.